Filsafat Spiritualitas: Memahami Perubahan Hidup Dalam Konteks Alkitab - Jefri Feoh; Reni Marlince Adang; Mozes Lawalata (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Life change is an inevitable process in every individual's journey. This paper explores how the principles of spirituality and biblical teachings can provide guidance and meaning in experiencing positive and meaningful life change. Spirituality is viewed as a search for a higher purpose in life, both from a philosophical and Christian religious perspective. The Bible contains many narratives of characters who underwent significant life transformations, such as Paul and Mary Magdalene. Biblical teachings emphasize principles such as repentance, renewing of the mind, living in the Spirit, and sanctification to achieve true life transformation. Philosophy also offers interpretations that enrich the understanding of spirituality and life change, such as the concept of self-denial, achieving higher consciousness, and the pursuit of a more noble life purpose. To experience positive life change, steps such as self-evaluation, goal setting, action planning, self-discipline, and support from a faith community are necessary. The faith community plays a crucial role in providing moral support, accountability, role models, guidance, and resources for its members going through the process of life transformation.